Key nuclear data for non-LWR reactivity analysis - Bostelmann, Friederike; Ilas, Germina; Wieselquist, William A. (Frontiers in Energy Research, 2023)
An assessment of nuclear data performance for non–light-water reactor (non-LWR) reactivity calculations was performed at Oak Ridge National Laboratory that involved a thorough literature review to collect related observations made across different research institutions, an interrogation of the latest ENDF/B evaluated nuclear data libraries, and propagation of nuclear data uncertainties to key figures of merit associated with reactor safety for six non-LWR benchmarks. The outcome of this comprehensive study was published in a technical report issued by the the US Nuclear Regulatory Commission. This paper provides a summary of the study's key observations and conclusions and demonstrates with two examples how the various methods available in the SCALE code system were used to identify key cross section uncertainties for non-LWR reactivity analyses.